The recurrence of measles and polio myelitis due to vaccine abstention in Brazil: a literature review - Rolemberg, Mychelle Oliveira Carvalho; Radmann, Guilherme Corrêa; Lima, Lívia Cardoso; Bitencourt, Joana Alves; Abreu, Guilherme Caxico de; Galvão, Júlia Alves Valois; Gonçalves, Maria Fernanda dos Santos; Rocha, Emanuelle Assunção Santos Costa da; Hora, Isaú Barreto; Farias, Any Eduarda Nanes de Oliveira; Carvalho, Felipe Mendes de Andrade de (JRG Journal of Academic Studies, 2024)
Introduction: Vaccine-preventable diseases have been a public health issue in Brazil since the creation of the National Immunization Program (PNI) in 1973, which aimed to reduce the incidence and eradicate transmissible infections, such as measles and poliomyelitis, among the country's population. However, in the last two decades, an increase in cases of these diseases has been observed, associated with various factors, such as vaccine hesitancy, particularly stemming from anti-vaccine movements spread across the country and the world. Objective: To provide a general overview of measles and poliomyelitis, investigating the causes and consequences associated with the recurrence of these diseases in Brazil. Methodology: This is a literature review conducted through searches in the SciELO, PubMed, and Latindex databases, using descriptors grouped by the boolean operator AND for the search. Original articles published between 2018 and 2024 in Portuguese and English were considered; those unrelated to the study object were excluded. Results and Discussion: The low vaccination coverage currently faced by Brazil, driven by anti-vaccine movements, fake news, lack of education, and religious precepts, leads to the recurrence of diseases previously eradicated, such as poliomyelitis and measles. This results in worrying consequences, such as the spread of infection with outbreaks and epidemics, severe complications secondary to the resurgence of diseases, impact on public health due to increased demand on the health system, and educational and social challenges, reinforcing the need to discuss the topic to raise vaccination rates and reduce associated morbidity and mortality. Conclusion: In summary, vaccine abstention against measles and poliomyelitis has a significant impact on public health by putting unvaccinated individuals at risk, as well as the general population, as these are contagious and fatal but preventable diseases.